Systematic Review of Stimulant and Nonstimulant Laxatives for the Treatment of Functional constipation - Pierre Paré; Richard N Fedorak (Canadian Journal of Gastroenterology and Hepatology)
BACKGROUND: Constipation is an uncomfortable and common condition that affects many, irrespective of age. Since 1500 BC and before, health care practitioners have provided treatments and prevention strategies to patients for chronic constipation despite the significant variation in both medical and personal perceptions of the condition.